Precision multi-response optimization of performance characteristics in wire-cut electric discharge machining (WEDM) process / I. Nayak and J. Rana - Nayak, I.; Rana, J. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
In this paper, an effective two stage multi-response optimization technique (i.e. grey relational analysis coupled with Taguchi technique) has been applied to achieve a better performance characteristic in wire-cut electrical discharge machining (WEDM) process. A zinc coated brass wire of 0.25 mm diameter was used as tool electrode for machining a D2 tool steel specimen. Experiments were planned according to Taguchi’s L9 orthogonal array under different cutting parameters such as: pulse on time (TON), pulse off time (TOFF), peak current (IP) and wire feed rate (WF). The three quality characteristics (i.e. performance characteristics), namely cutting rate, kerf width and surface roughness have been simultaneously optimized in two different stages. It wasobserved that the cutting speed is increased by 24.60% compared to first stage/primary optimization process. From the analysis of variance (ANOVA), pulse-on time is found to be the most influencing cutting parameter having 74.91% contribution towards overall performance of the WEDM process. Finally,a confirmatory experiment has been carried out at optimum set of cutting parameters obtained from the precision optimization stage to identify the effectiveness of this proposed method. It was observed that the predicted values of the responses obtained from regression models were in good agreement with the experimental findings.